Tracing the Propagation of Shocks in the Equatorial Ring of SN 1987A over Decades with the Hubble Space Telescope - Christos Tegkelidis; Josefin Larsson; Claes Fransson (The Astrophysical Journal)
The nearby SN 1987A offers a unique opportunity to investigate the complex shock interaction between the ejecta and circumstellar medium. We track the evolution of the optical hot spots within the equatorial ring (ER) by analyzing 33 Hubble Space Telescope imaging observations between 1994 and 2022. By fitting the ER with an elliptical model, we determine its inclination to be 42.°85 ± 0.°50 with its major axis oriented −6.°24 ± 0.°31 from the west. We identify 26 distinct hot spots across the ER, with additional ones emerging over time, particularly on the western side. The hot spots initially show high velocities ranging from 390 to 1660 km s ^−1 , followed by a deceleration phase around day ∼ 8000. Subsequent velocities vary from 40 to 660 km s ^−1 . The light curves of the hot spots reach maxima between 7000 and 9000 days, suggesting a connection with the deceleration. Many spots are spatially resolved and show elongation perpendicular to the direction of motion, indicative of a short cooling time. To explain these results, we propose that each hot spot comprises dense substructures embedded in less dense gas. The initial velocities are then phase velocities, where the break occurs when the blast wave leaves the ER, while the late velocities reflect the propagation of radiative shocks in the dense substructures. We estimate that the dense substructures have a volumetric filling factor of $\sim 0.3{\left({n}_{{\rm{e}}}/{10}^{6}\ {cm}^{-3}\right)}^{-2} % $ and a total mass of $\sim 0.24{\left({n}_{{\rm{e}}}/{10}^{6}\ {cm}^{-3}\right)}^{-1}× {10}^{-2}\ M_{\odot }$ .